BARRIERS AND ENABLERS OF A REPORTING CULTURE: A SYSTEMATIC REVIEW OF PATIENT SAFETY INCIDENT REPORTING BY HOSPITAL HEALTHCARE WORKERS - Cyrilla Ayu Pamela; Trihaningsih Puji Astuti; Vira Amelia (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Background: Patient safety incidents remain common in hospitals and directly affect the quality of healthcare services. Incident reporting is a key strategy for improving service quality and promoting a safety culture. An effective reporting culture requires the reduction of barriers and the strengthening of enabling factors so that healthcare workers feel safe to report incidents. Purpose: This systematic review aimed to identify barriers and supportive factors affecting the establishment of a patient safety incident reporting culture among healthcare personnel within hospital environments. Methods: A systematic review was undertaken through a comprehensive search of four databases, including ScienceDirect, ProQuest, PubMed, and. Google Scholar. The search terms were: (